A DTAP-IPV//PRP~T VACCINE: A REVIEW OF 16 YEARS' CLINICAL EXPERIENCE - Stanley A. Plotkin; Johannes Liese; Shabir A. Madhi; Esteban Ortiz ("Paediatrician" Publishers LLC, 2012)
Owing to their low reactogenicity, confirmed efficacy and availability in combination vaccines, acellular pertussis (aP)-inactivated poliovirus (IPV) combined vaccines are now included in various national immunization programs worldwide. We provide an overview of 16 years of clinical experience with a diphtheria (D), tetanus (T), aP, IPV and Haemophilus influenzae type b (Hib) polysaccharide conjugated to tetanus protein (PRP~T) combined vaccine (DTaP-IPV//PRP~T - Pentaxim, Sanofi Pasteur, France). Good immunogenicity has been demonstrated after primary vaccination with Pentaxim, regardless of the population ethnicity and primary vaccination schedule. A booster vaccination in the second year of life also resulted in a high immune response for each antigen. Furthermore, 10 years of national surveillance in Sweden has demonstrated the effectiveness of Pentaxim in controlling pertussis. As is the case for other aP-containing combined vaccines, Pentaxim is well tolerated, with the safety profile being better than for whole-cell pertussiscontaining combination vaccines for primary and booster vaccinations.